O retrato de Deus: representações de Deus em crianças, colhidas através de técnicas projetivas gráficas e verbalizações - Rocha, Márcia Christovam da Silva (2005)
The present work aims to show the representations of God revealed by the projections of two children, a boy and a girl, through graphic projection technique followed by verbalization. The material collected consists of seven drawings through which the children answer to two stimulus questions: Who is God? ; Where does God live? . With this work the author intends to know the representations that these children have built concerning the figure of God, analyzing the drawings, the speeches and their signification, within the reference of the projective technique analysis. The archetypal symbolic memory of the ancient traditions of the humanity, specially the christian-jewish tradition and theology are the riddle of lecture and analysis of the collected material, which was the source of information about the representation concerning the rational aspect of the psychic apparatus, social building of the cognitive and semantic system traced by the social and cultural background, and as projective expression of the archetypes of the collective unconscious.